PENTINGNYA KOMPETENSI GURU GUNA MENGHADAPI SISTEM REKRUTMEN BARU “MARKETPLACE GURU” - Nadif Maialfatih (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The Ministry of Education, Culture, Research and Technology, Nadiem Anwar Makarim issued a new recruitment system, namely the "teacher marketplace". The teacher marketplace is a place where all teachers who are allowed to teach are entered into a data repository (database) that can be accessed by all schools in Indonesia. The "teacher marketplace" system makes it easy for schools to "compare" teachers with other teachers who have the same area of expertise based on their competencies. This article was created with the aim of providing an overview of the "teacher marketplace" and explaining what competencies prospective teachers must have in order to deal with this new recruitment system. Teacher competences includes pedagogic, personality, social, and professional. By mastering these four competencies, teachers are expected to improve their quality and can be easily selected by the school.